Psychological Dynamics of Premeditated Murder Convicts in Early Age - Maya .; Sitti Murdiana; Perdana Kusuma (Polteknik Ilmu Pemasyarakatan, 2023)
Premeditated murder is a criminal act of murder that is carried out with planning and preparation before killing the victim, especially referring to the existence of a period of time before acting to commit or cancel the risky action. This study aims to determine the factors that can influence someone to commit premeditated murder, as well as the impact experienced and felt by the perpetrator after the incident. Respondents in this study were convicts who were convicted of premeditated murder, aged 18-40 years, and who were in Class 1 Penitentiary in Makassar City. This study uses a qualitative method with a case study design. Data collection techniques using interviews and documentation. The results showed that the factors that influenced aggression led to premeditated murder, namely first, the background of HBH respondent (33) in the form of conditions and family relations which indicated indulgent parenting, negative social interactions, the principle of siri'na pacce which had long been taught and upheld by HBH respondents. Second, based on the chronology of events in the form of provocation, remembering the teachings of siri' na pacce, and awakening or arousal. The impact is in the form of a sentence of twenty years in prison, destruction of the house and family transportation, involvement of a younger sibling and father who was sentenced to sixteen years in prison so they feel guilty, divorce, and are still haunted by the murder incident, especially the expression of the victim when the date of the incident was approaching, causing difficulties sleep.